(untitled) (Global Journal of Human-Social Science, 2012)
Part of the intellectual legacy left behind by David Hume is a powerful skeptical argument which casts doubts on the validity or more appropriately justification of a basic form of inductive inference Brian Skyrms and Laurence Bonjour have outlined several possible defenses of what they call the inductive principle IP in response to the broader Humean challenge In this paper I elaborate Skyrms inductive justification and pragmatic defense of IP as well as Bonjour s novel a priori argument for IP In the course of critically assessing the cogency of these three strategies I argue that each one is problematic and fails to provide an adequate defense of IP I conclude by briefly considering what would be minimally required for a serious rebuttal to the skeptical argument